The role of horticultural package vent hole design on structural performance - Fadiji, T.; Berry, T.; Coetzee, C.; Opara, U. L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Globally, ventilated paperboard packaging has been widely utilised particularly in the horticultural industry to protect packed produce against damage to satisfy consumer needs. During postharvest activities, the packages are exposed to cold environment and mechanical hazards. The mechanical hazards may result from different loadings such as drop, impact, vibration, compression or a combination of all. Designing ventilated packages should be such that they can provide uniform air distribution to cool the packed produce and protect the produce against mechanical damage. However, the presence of vent holes causes material loss of the package, thereby reducing the stacking strength of the packages and consequently resulting in produce damage. The strength of the package is crucial for preserving the produce and therefore optimising the package is essential to save time, money and resources. This research was aimed at evaluating the structural behaviour of ventilated packages. Finite element analysis was used to create models to study the buckling of three ventilated package designs when subjected to compression load. Packages with different vent area and paperboard grades were studied. Experiments were used to quantify box compression strength. Results of mechanical strength evaluation showed a negative linear relationship between carton strength and vent area. Board thickness increased the compression strength of the packages. At 2% and 4% vent areas, packages with C flute board reduced in strength by as high as 46% when compared with the strength of the packages with B flute board. Numerical results and experimental results were in good agreement, within 12%. This study suggests the need for alternative package designs, considering the mechanical strength while still providing proper and adequate ventilation to the packed produce.